2020
DOI: 10.1002/adsc.202000356
|View full text |Cite
|
Sign up to set email alerts
|

Benzylic C−H Functionalisation by [Et3SiH+KOtBu] leads to Radical Rearrangements in o‐tolyl Aryl Ethers, Amines and Sulfides

Abstract: Reaction of Et 3 SiH + KO t Bu with diaryl ethers, sulfides and amines that feature an ortho alkyl group leads to rearrangement products. The rearrangements arise from formation of benzyl radicals, likely formed through hydrogen atom abstraction by triethylsilyl radicals. The rearrangements involve cyclisation of the benzyl radical onto the partner arene, which, from computation, is the rate determining step. In the case of diaryl ethers, Truce-Smiles rearrangements arise from radical cyclisations to form 5-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Notably, it can add to arene rings in the substrate to generate intermediates 49 that feature a labile H atom. [2][3][4][5][6]13 This can react with a silyl radical 45 to form trimethylsilane or with silyl anion 46 to form trimethylsilane as shown in Scheme 5. This would mean that the missing trialkylsilane reagent (Me 3 SiH in this experiment) would be generated in situ, starting from the disilane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, it can add to arene rings in the substrate to generate intermediates 49 that feature a labile H atom. [2][3][4][5][6]13 This can react with a silyl radical 45 to form trimethylsilane or with silyl anion 46 to form trimethylsilane as shown in Scheme 5. This would mean that the missing trialkylsilane reagent (Me 3 SiH in this experiment) would be generated in situ, starting from the disilane.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that benzylic C-H bonds can undergo abstraction of an H-atom under the conditions of these reactions, by triethylsilyl radicals 1. 13 In this case, this would lead to radical 105 (Scheme 12). Cyclopropylcarbinyl radical rearrangement would lead to ringexpansion to radical 107, which, following deprotonation, would expel a benzyl radical to yield quinoline anion 109.…”
Section: Edge Article Chemical Sciencementioning
confidence: 99%
See 1 more Smart Citation